Analisis Dampak Kawasan Industri Terhadap Lingkungan Masyarakat di Kecamatan Gunungputri - Wibowo, Aryo; Kusumawati, Niken Aulia; Athira, Yukova Miska; Ananda, Putry; Antoni, Herli (Pemuliaan Hukum, 2023)
Industry is one of the most important sectors in developing the Indonesian economy. This sector has become the largest supply tool in increasing the country's GDP for approximately the last 10 (ten) years, especially with the establishment of industrial estates or areas in an area. The industrial estate is a central place for all manufacturing or industrial activities complete with adequate infrastructure, then managed by companies in the industrial estate. The establishment of an area in an area can have an impact on the environment around the industrial area, such as people who feel disturbed by the negative impacts resulting from the industrial area in the form of pollution and environmental pollution in the residential areas of the surrounding community, but in addition to the negative impact of the existing industrial area always coexists also with a positive impact, one example of the positive impact of the development of the local community's economic sector. This research aims to elaborate the impact of the existence of industrial estates on the community environment around the Gunungputri sub-district industrial area. This research uses Normative research by identifying legislation related to the research theme.Industri merupakan satu dari sekian sektor penting dalam membangun perekonomian Indonesia. Sektor ini menjadi alat suplai terbesar dalam peningkatan PDB negara selama kurang lebih 10 (sepuluh) tahun terakhir, apalagi dengan berdirinya kawasan atau wilayah industri di suatu daerah. Kawasan industri merupakan tempat sentral segala aktivitas manufaktur atau industri yang lengkap dengan sarana-prasarana yang memadai, kemudian diurus oleh perusahaan dalam kawasan industri tersebut. Berdirinya kawasan disuatu wilayah dapat memberikan dampak terhadap lingkungan sekitar kawasan industri, seperti masyarakat yang merasa terganggu dengan dampak negatif yang dihasilkan dari kawasan industri berupa polusi dan pencemaran lingkungan di wilayah pemukiman masyarakat sekitar, namun disamping dampak negatif dari kawasan industri yang ada selalu berdampingan juga dengan dampak positif salah satu contoh dampak postif berkembangnya sektor perekonomian masyarakat setempat. Penelitian ini bertujuan mengelaborasi dampak keberadaan kawasan industri di lingkungan masyarakat sekitar kawasan industri kecamatan Gunungputri. Penelitian ini merupakan penelitian Normatif dengan identifikasi terhadap peraturan perundang-undangan yang berkaitan dengan tema penelitian.